Effect of carbohydrate source on fermentation by equine cecal microorganisms and effect of Enogen® Feed Corn on finishing pig growth performance and carcass characteristics - Ochonski, Patricia (Kansas State University, 2021)
Commercial horse feeds utilize cereal grains and byproducts; however, their effects on the cecal environment remain poorly characterized. Six cecally cannulated Quarter horses were used in a 6 × 6 Latin square in order to characterize the effect of commonly used feed ingredients on cecal pH and volatile fatty acid (VFA) concentration. On d -2, horses were moved into individual stalls where Smooth bromegrass hay (brome) was offered at 2.0% BW/d split between 2 feedings (0600 and 1800). On d 0, cecal digesta was collected every 2 h for 12 h relative to the 0600 feeding to establish control values for horses consuming only brome (HAY). On d 1, horses began consuming their respective treatments which consisted of beet pulp (BP), maize (M), dehydrated alfalfa (A), oats (OAT), soybean hulls (SBH), or wheat middlings (WM) at 0.25% BW/d split into 2 feedings. On d 7 of each treatment period, cecal digesta was collected every 2 h for 12 h and analyzed for pH and VFA. Data were analyzed using mixed ANOVA with repeated measures, fixed effects of treatment and time, and random effects of horse and period. There was a main effect of hour (P ≤ 0.05) indicative of post-prandial shifts in cecal metabolites. There were no main effects of treatment on pH or VFA concentration (P ≥ 0.31). Effects of hour × treatment (P < 0.042) were observed for all response variables. Regardless of treatment or hour, cecal pH remained well within normal limits. Three horses exhibited signs of lower esophageal choke immediately after consumption of BP pellets. Overall, minimal differences in cecal fermentation parameters were detected when ingredients were fed at a common inclusion level. Overconsumption of dietary starch is associated with increased risk of hindgut acidosis and subsequent development of gastrointestinal and metabolic disorders. Researchers have suggested that the upper limit of small intestinal starch digestion is 2 to 4 g starch·kg BW⁻¹·meal⁻¹. The objectives of this trial were to determine the effect of increasing levels of dietary starch on the cecal environment and voluntary forage dry matter intake (DMI). Six cecally cannulated Quarter horses (8-13 yr; 524 ± 65.5 kg BW) were used in a dose titration style design. Before the study began, horses were maintained in a single dry lot pen and offered ad libitum Smooth bromegrass hay (brome). On d -14, horses were moved to individual stalls and provided brome hay ad libitum and a ration balancer (0.0125% BW 4x/day). On d 0, cecal digesta samples were collected every 2 h for 12 h relative to the 0600 feeding. On d 1, pelleted corn (69.4% starch) was offered at 0.5 g starch·kg BW⁻¹·meal⁻¹at 0600, 1200, 1800, and 2400 h. Every 8 d thereafter, corn was increased to provide an additional 0.5 g starch·kg BW⁻¹·meal⁻¹ until horses were consuming 3.5 g starch·kg BW⁻¹·meal⁻¹. Seven days following each increase in dietary starch, the cecal sampling protocol was repeated. Cecal pH was recorded upon sample collection. Cecal digesta was analyzed for volatile fatty acids (VFA) via gas chromatography, and lactate via a colorimetric procedure. Data were analyzed as a randomized complete block design with repeated measures, with fixed effects of treatment and time and random effect of horse. There was an effect of treatment on forage DMI (P ≤ 0.0001). As dietary starch increased, forage DMI decreased. Greatest total DMI (P ≤ 0.041) was recorded when horses were offered 3.0 g starch. It should be noted that horses did not consume the full meal for treatments 2.5, 3.0, and 3.5 g starch, and on average consumed 2.1, 2.72, and 2.68 g starch·kg BW⁻¹·meal⁻¹ (respectively). Effects of treatment, hour, and treatment × hour were observed (P ≤ 0.032) for pH, acetate, propionate, acetate:propionate, and total VFA concentration. Cecal pH decreased as dietary starch increased, with lowest pH observed with 2.0 g starch (P < 0.0001). Cecal propionate and total VFA concentration were greatest (P < 0.0485) for 2.0 and 2.5 g. Acetate:propionate ratio was lower (P ≤ 0.005) for 2.0 g starch compared to ≤ 1.5 g treatments; however, A:P did not continue to decrease with additional starch. Cecal acetate, propionate, butyrate, and total VFA concentrations were lowest (P < 0.0001) when horses were fed 3.5 g starch. Cecal lactate concentration was greatest (P < 0.0060) when horses were fed 2.0 g starch and lowest (P < 0.0001) for horses consuming 0 and 0.5 g starch. This trial demonstrates that voluntary forage DMI decreases with increasing levels of starch, as previously observed in ruminants. Consumption of ≥ 2.0 g starch·kg BW⁻¹·meal⁻¹ may lead to shifts in cecal microbial communities that result in decreased fermentative activity. However, even when horses were offered ≥ 2.0 g starch·kg BW⁻¹·meal⁻¹ cecal acidosis was not observed. Enogen® Feed Corn (EFC; Syngenta Seeds, LLC, Downers Grove, IL) hybrids contain a trait for expression of heat-stable alpha amylase in the grain. Alpha amylase is an enzyme responsible for breakdown of starch in the small intestine; supplementation of exogenous alpha amylase to pigs may result in greater starch digestibility and thus improved gain efficiency. A total of 288 pigs (Line 600 × 241, DNA, Columbus, NE; initially 41.6 kg) were utilized in an 82-d trial to determine if replacing conventional yellow dent corn (CONV) with EFC in diets with or without distillers dried grains with solubles (DDGS) influences growth performance and carcass characteristics. Pens of pigs were randomly assigned to 1 of 4 dietary treatments balancing for initial BW. There were 9 pens per treatment with 8 pigs per pen (an equal number of barrows and gilts per pen). Treatments were arranged in a 2 × 2 factorial with main effects of corn source (CONV or EFC) and DDGS (0 or 25%). Experimental diets were fed in meal form in 3 phases: d 0 to 29, 29 to 47, and 47 to 82. Pigs were weighed approximately every 2 wk and at the beginning of each phase. On d 82, pigs were transported to a commercial abattoir for processing and carcass data collection. Data were analyzed using PROC GLIMMIX procedure of SAS with pen as the experimental unit. There were no corn source by DDGS interactions (P > 0.05) observed for overall performance or carcass characteristics. Overall, average daily gain (ADG) was marginally greater (P < 0.089) for pigs fed EFC than CONV with no evidence (P > 0.196) for difference in average daily feed intake (ADFI), gain efficiency (G:F), hot carcass weight (HCW), or other carcass traits. Addition of DDGS decreased (P < 0.047) overall ADG and G:F. Pigs fed DDGS had marginally lower (P < 0.071) HCW, less (P < 0.050) backfat depth, greater (P < 0.026) loin depth, and greater (P < 0.020) percentage lean and carcass fat iodine value (IV). In summary, addition of 25% DDGS to the diet decreased ADG and increased carcass fat IV. Pigs fed EFC tended to have improved overall ADG; however, G:F and carcass characteristics were not different between corn sources. These results suggest that EFC, although not beneficial, may be used as a substitute for CONV without any deleterious effects on growth performance. Further research should be conducted to understand if addition of EFC to swine diets could be beneficial in younger pigs exhibiting decreased pancreatic α-amylase secretion following weaning, or whether heat treatment of diets, such as pelleting, may influence the response to EFC.
Keywords: Horse; Cecum; Acidosis; Starch; Finishing pig; DDGS